2019
DOI: 10.1038/s41419-019-1820-x
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition-mediated epithelial–mesenchymal transition augments local myofibroblast differentiation in pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF), the prototypic progressive fibrotic interstitial lung disease, is thought to be a consequence of repetitive micro-injuries to an ageing, susceptible alveolar epithelium. Ageing is a risk factor for IPF and incidence has been demonstrated to increase with age. Decreased (macro)autophagy with age has been reported extensively in a variety of systems and diseases, including IPF. However, it is undetermined whether the role of faulty autophagy is causal or coincidental in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
127
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(133 citation statements)
references
References 61 publications
(93 reference statements)
6
127
0
Order By: Relevance
“…(Macro) autophagy is where a double-membraned vesicle is formed, which captures material in the cytoplasm to be degraded, whereas selective autophagy specifically targets cargo to be degraded [12][13][14][15] . Autophagy has also been proposed to have roles in a number of diseases [16] , such as fibrosis [17][18][19] , neurodegeneration [20] and cancer [21,22] [ Figure 2].…”
Section: Autophagymentioning
confidence: 99%
“…(Macro) autophagy is where a double-membraned vesicle is formed, which captures material in the cytoplasm to be degraded, whereas selective autophagy specifically targets cargo to be degraded [12][13][14][15] . Autophagy has also been proposed to have roles in a number of diseases [16] , such as fibrosis [17][18][19] , neurodegeneration [20] and cancer [21,22] [ Figure 2].…”
Section: Autophagymentioning
confidence: 99%
“…Finally, our results suggest that macrophagic autophagy can facilitate brosis. Although not in accordance with the initial acceptance that autophagy might be protective in lung brosis (11,13,28), our data are in line with more recent results from the literature showing an increased number of LC3-II puncta, an index of active autophagy, in broblast foci of patients with idiopathic pulmonary brosis (IPF), the most common form of pulmonary brosis (13,29). In vitro, these authors also showed that autophagy is induced by TGFß, and that it is necessary for TGFß-induced brosis in both non-IPF and IPF broblasts (7).…”
Section: Discussionmentioning
confidence: 78%
“…In vitro, these authors also showed that autophagy is induced by TGFß, and that it is necessary for TGFß-induced brosis in both non-IPF and IPF broblasts (7). Interestingly, such a cell-speci c role for autophagy has been recently described in chronic obstructive pulmonary disease (COPD) where autophagy is believed to be protective except in macrophages (10)(11)(12)28). In lung brosis, the majority of the studies has focused on lung epithelial cells and/or broblasts (28), as the two major cell type involved in brogenesis (15).…”
Section: Discussionmentioning
confidence: 92%
“…Autophagy plays a pivotal role in attenuating fibrosis. 21,22 To determine if ONG41008 could induce the induction of autophagosomes, DHLFs and ONGHEPA1 cells were treated with TGF plus ONG41008, resulting in the complete inhibition of fibrosis and of autophagosome production ( Figure 4A). Western blotting of ONGHEPA1 cell lysates with a cleavage-specific anti-LC3 antibody showed fragmentation of LC3 protein, generating A/B polypeptide fragments ( Figure 4B).…”
Section: Resultsmentioning
confidence: 99%